Two newly recorded invasive alien ascidians (Chordata, Tunicata, Ascidiacea) based on morphological and molecular phylogenetic analysis in Korea - Pyo, Jooyeon; Lee, Taekjun; Shin, Sook (Zootaxa, 2012)
We report five alien ascidians with some distinct features that were investigated from August 2009 to October 2011 in Korea, among which Ascidiella aspersa (Müller, 1776) belonging to family Ascidiidae of order Phlebobranchia and Molgula manhattensis (De Kay, 1843) belonging to family Molgulidae of order Stolidobranchia are newly discovered invasive species. These ascidians were identified and their phylogenetic relationships were clarified through molecular analysis using about 680 bp of nuclear 18S rDNA and about 670 bp of mt-COI genes along with detailed morphological characteristics, and reported for the first time in Korea. It was discovered that A. aspersa was widespread three coastlines of Korea except Jeju Island, and M. manhattensis first found in Mokpo, Gunsan, and Incheon in June 2010 extended into Busan of Korea Strait in 2011.